Thermal stress tolerance in different cultivars of Coffea arabica L.: Implications in the context of climate change in Colombia (2024)
Coffea arabica L. is a crucial agricultural product in Colombia, ranking as the second most traded commodity worldwide. This sector is vital for the livelihoods of over 540,000 families, with coffee cultivation extending across 600 municipalities in 23 coffee-growing departments. The Ministry of Agriculture reports that coffee contributes 15% to the Colombian agricultural GDP, generating approximately 2.5 million direct and indirect jobs. In the Colombian context, assessing plant thermal resistance in agricultural crops has become increasingly significant due to climate change. Thermal stress poses a serious threat to biodiversity and agricultural production, endangering suitable habitats for cultivating C. arabica. Understanding how this species responds to rising temperatures is essential for adaptation to future climate scenarios. The purpose of this study is to quantify how different varieties of C. arabica respond to high temperature stress. Eight different varieties of C. arabica were studied: Bourbon, Castillo, Caturra, Cenicafe 1, Colombia, Geisha, Tabi and Typica. Maximum quantum efficiency of photosystem II (Fv/Fm) measurements were taken on leaves of plants subjected to different temperatures between 20 and 50°C to determine their corresponding injury temperatures (T50). This temperature corresponds to a 50% reduction in Fv/Fm values measured as a function of the reference 20°C temperature. Additionally, the thermal safety margin was calculated for different coffee-producing municipalities of Colombia comparing the T50 values with the maximum air temperature of sites obtained from the Agroclima database. This research reveals significant differences in T50 among various C. arabica varieties, with Caturra and Typica exhibiting greater thermal stress tolerance. Current climatic conditions in the studied municipalities do not exceed the T50 of these varieties, indicating no harmful temperatures. However, with climate change predicting increased extreme temperature events, the higher T50 for Caturra and Typica are crucial for enhancing coffee crop resilience and stability. Despite previous studies suggesting temperature sensitivity in Arabica coffee, this research shows that it can tolerate heat stress up to 42°C, maintaining photosynthetic efficiency up to 40°C. This challenges the notion that Arabica coffee lacks thermal resilience.